How Many Varieties of Capitalism? Comparing the Comparative Institutional Analyses of Capitalist Diversity - Gregory Jackson; Richard Deeg (Max Planck Institute for the Study of Societies, 2006)
This essay reviews the development of approaches within the comparative capitalisms (CC) literature and points to three theoretical innovations which, taken together, define and distinguish these approaches as a group. First, national economies are characterized by distinct institutional configurations that generate a particular systemic 'logic' of economic action. Second, the CC literature suggests a theory of comparative institutional advantage in which different institutional arrangements have distinct strengths and weaknesses for different kinds of economic activity. Third, the literature has been interpreted to imply a theory of institutional path dependence. Behind these unifying characteristics of the literature, however, lie a variety of analytical frameworks and typologies of capitalism. This paper reviews and compares these different frameworks by highlighting the fundamental distinctions among them and drawing out their respective contributions and limitations in explaining economic performance and institutional dynamics. The paper concludes that the way forward for this literature lies in developing a more dynamic view of individual institutions, the linkages between domains, and the role of politics and power. – – In diesem Discussion Paper werden Ansätze der Comparative-Capitalism-Diskussion vorgestellt. Sie haben drei theoretische Innovationen gemein. Erstens: Nationale Ökonomien werden durch institutionelle Konfigurationen geprägt, die auf jeweils eigene "systemische Logiken" wirtschaftlichen Handelns hinwirken. Zweitens: Die Comparative-Capitalism-Literatur beinhaltet eine Theorie der komparativen institutionellen Vorteile, der zufolge institutionellen Konfigurationen spezifische Wettbewerbsvorteile zugeordnet werden können. Zudem, drittens, beinhaltet die Comparative-Capitalism-Literatur auch eine implizite Theorie der Pfadabhängigkeit. Trotz dieser Gemeinsamkeiten unterscheiden sich die Ansätze hinsichtlich analytischer Zugriffe und Vorschläge zur Typologisierung nationaler Kapitalismen. Beim Vergleich dieser Ansätze werden besonders deren Stärken und Schwächen bei der Analyse wirtschaftlicher Performanz und institutioneller Entwicklungsdynamiken hervorgehoben. Der Aufsatz kommt zu dem Schluss, dass die Comparative-Capitalism-Literatur in dreierlei Hinsicht der Weiterentwicklung bedarf: hinsichtlich einer dynamischeren Modellierung von Institutionen, einem besseren Verständnis der Interaktion institutioneller Domänen und der Berücksichtigung von Macht und Politik in der Analyse von Produktionsregimen.
Keywords: 300